Democracy in Southeast Asia: A year of Elections - RICKS, Jacob (Institutional Knowledge at Singapore Management University, 2019)
I n the year from May 2018 to May 2019, 6 of the 11 Southeast Asian states held major elections. The outcomes demonstrate the broad and mixed uses and impacts elections have in the region, ranging from what many consider to be a major democratization event in Malaysia wherein a coalition of opposition parties finally unseated the long-standing Barisan Nasional (BN), to the continued consolidation of single-party rule in Cambodia under Hun Sen’s Cambodian People’s Party (CPP). With so many elections happening in short order, we at Asian Politics & Policy felt that this is an opportune moment to compile a set of perspectives on these elections, based on a single theme. We reached out to an exciting group of junior scholars on Southeast Asia, all of whom have conducted extensive fieldwork in their countries of specialization in recent years. We asked each of these six path-breaking researchers to briefly address the election, discuss its impact, and offer an evaluation on the state of democracy in the country. Their responses are found below, chronologically ordered by election date.